Could fighting airborne transmission be the next line of defence against COVID-19 spread?. (December 2019) - Kumar, Prashant; Morawska, Lidia
Abstract: The World Health Organization declared the infectious spread of SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2) an epidemic during its initial outbreak in Wuhan (China) and has since declared it a pandemic and, more recently, an endemic infection that may remain in our communities. A vaccine for COVID-19 is expected to take several months, meaning that the spread may continue in future, in the absence of the most effective measures of social distancing and self-isolation. While these measures have worked well under lockdowns, the potential of airborne transmission of COVID-19 under the eased restrictions has not been considered important enough. We discuss the need to acknowledge the airborne spread of COVID-19 inside built spaces under eased movement restrictions and the potential steps that can be taken to control it. Highlights: Potential of COVID-19 spread via airborne pathway is discussed. Airborne transmission under eased movement restrictions needs acknowledging. A three-pronged approach to limit airborne transmission is proposed. Need to minimise build-up of virus-laden air in places with high densities of people is emphasised. Clear guidelines are required on short-term or situation-specific use of masks.